Effects of Intravitreal Aflibercept on the Systemic Insulin-like Growth Factor-I and Vascular Endothelial Growth Factor-A in Patients with Diabetic Retinopathy and Age-Related Macular Degeneration - Anna Lena Huber; Reinhard Angermann; Yvonne Nowosielski; Christof Seifarth; Martina T. Kralinger; Claus Zehetner (Journal of Ophthalmology)
Purpose. To analyze the effect of intravitreal aflibercept injections on systemic levels of insulin-like growth factor-1 and vascular endothelial growth factor-A in patients with diabetic retinopathy and age-related macular degeneration. Methods. Vascular endothelial growth factor-A and insulin-like growth factor-1 levels were determined before and one week and four weeks after intravitreal injection of aflibercept (2.0 mg/50 μl) for 19 patients with age-related macular degeneration (mean age, 76 ± 11 years) and 18 patients with diabetic retinopathy (mean age, 64 ± 14 years). Twenty-two healthy individuals were enrolled as controls. Results. A significant decline in systemic vascular endothelial growth factor-A level, from 43 (30–57) pg/ml at baseline to 8 (8–8) pg/ml (p<0.001) at week one and 17 (8–25) pg/ml (p=0.0054) at week four, was observed in the age-related macular degeneration group. In the diabetic retinopathy group, vascular endothelial growth factor-A levels declined from 53 (35–117) pg/ml to 2 (1–5) pg/ml (p<0.0001) one week after injection and 16 (13–22) pg/ml four weeks after injection (p=0.0327). At baseline, systemic insulin-like growth factor-1 concentration was higher in the diabetic retinopathy group (57 [37–99] pg/ml) than in the age-related macular degeneration group (35 [24–51] pg/ml) (p=0.0056). A subgroup analysis showed that patients in the proliferative diabetic retinopathy subgroup had significantly higher systemic insulin-like growth factor-1 concentrations (71 [44.7–243] pg/ml) than those in the nonproliferative diabetic retinopathy subgroup (43 [29–66] pg/ml) (p=0.0048). Conclusions. The difference between the baseline systemic insulin-like growth factor-1 levels of the age-related macular degeneration and diabetic retinopathy groups and the higher insulin-like growth factor-1 levels in the proliferative diabetic retinopathy subgroup one week after aflibercept therapy suggest that insulin-like growth factor-1 may play a role in the pathomechanism of diabetic retinopathy.